2013
DOI: 10.1073/pnas.1304749110
|View full text |Cite
|
Sign up to set email alerts
|

Conformations of intrinsically disordered proteins are influenced by linear sequence distributions of oppositely charged residues

Abstract: The functions of intrinsically disordered proteins (IDPs) are governed by relationships between information encoded in their amino acid sequences and the ensembles of conformations that they sample as autonomous units. Most IDPs are polyampholytes, with sequences that include both positively and negatively charged residues. Accordingly, we focus here on the sequenceensemble relationships of polyampholytic IDPs. The fraction of charged residues discriminates between weak and strong polyampholytes. Using atomist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

79
1,353
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 879 publications
(1,439 citation statements)
references
References 42 publications
79
1,353
7
Order By: Relevance
“…This pI-centred swelling behaviour has been previously observed for synthetic polyampholytes with charges randomly distributed along their length, which displayed at least threefold higher degree of swelling than mixed brushes of oppositely charged polyelectrolytes 36,37 . Recombinantly redistributing local charge density within rNFH-SA may offer additional opportunities to expand and tune these swelling dynamics 38 .…”
Section: Resultsmentioning
confidence: 99%
“…This pI-centred swelling behaviour has been previously observed for synthetic polyampholytes with charges randomly distributed along their length, which displayed at least threefold higher degree of swelling than mixed brushes of oppositely charged polyelectrolytes 36,37 . Recombinantly redistributing local charge density within rNFH-SA may offer additional opportunities to expand and tune these swelling dynamics 38 .…”
Section: Resultsmentioning
confidence: 99%
“…PEG is widely used for biomedical applications (31) and for mimicking inert crowding agents (13,26). Previous work has shown that the conformational properties of IDPs strongly depend on their amino acid sequence composition and charge patterning (8,11,27,28,(32)(33)(34). Here we investigate the effect of crowding on four different IDP sequences that span a broad range of net charge per residue and average hydrophobicity ( Fig.…”
mentioning
confidence: 99%
“…16,18,46 Small Angle X-ray Scattering 47,48 or single-molecule fluorescence 28,49-51 as well as employing atomistic and coarse-grained simulations. 20,[52][53][54][55] By using the above-mentioned techniques some approximations have been reported to design drugs targeting IDPs. The common approaches are (I) directly bind to the disordered ensemble neutralizing the protein function/dysfunction and (II) bind to a binding partner and inhibit IDP binding or stabilize its bound state.…”
Section: Drug Designmentioning
confidence: 99%